Enhanced access to healthcare utilization data through medical record review: Lessons learned from a community‐based, multi‐site project. Issue 4 (10th June 2021) - Grape, Annette; Wicks, Mona; Tumiel‐Berhalter, Laurene; Sloand, Elizabeth; Rhee, Hyekyun
Abstract: Collecting accurate healthcare utilization (HCU) data on community‐based interventions is essential to establishing their clinical effectiveness and cost‐related impact. Strategies used to enhance receiving medical records for HCU data extraction in a multi‐site longitudinal randomized control trial with urban adolescents are presented. Successful strategies included timely assessment of procedures and practice preferences for access to electronic health records and hardcopy medical charts. Repeated outreach to clinical practice sites to identify and accommodate their preferred procedure for medical record release and flexibility in obtaining chart information helped achieve a 75% success rate in this study. Maintaining participant contact, updating provider information, and continuously evaluating site‐specific personnel needs are recommended.